2022
DOI: 10.1155/2022/5498514
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant Indexes and Immune Function of the Intestinal Flora of Compound Microecological Preparations

Abstract: Compound probiotics are biological products made by mixing and cultivating various probiotics according to appropriate composition and ratio. It can not only play the role of a variety of probiotics in composition but also the effect of the ratio is often greater than the effect of the single strain alone. These probiotics are good for the body’s immune system in living organisms. They act as immune boosters in living organisms. They are considered the safest form of treatment. In this review, the effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Consequently, adding probiotics to animal diets can partially replace antibiotics in feed. Due to its green, nontoxic, safe, and effective properties, probiotic supplementation has been increasingly used in animal husbandry (Sun & Zhang, 2022). According to the types of microorganisms, they can be classified as Bacillus , Lactic acid bacteria , yeast, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, adding probiotics to animal diets can partially replace antibiotics in feed. Due to its green, nontoxic, safe, and effective properties, probiotic supplementation has been increasingly used in animal husbandry (Sun & Zhang, 2022). According to the types of microorganisms, they can be classified as Bacillus , Lactic acid bacteria , yeast, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus were significantly enriched in high‐FCR chickens and inhibited the abundance of pathogenic bacteria 33 . Exogenous probiotics have a subtle physiological effect on the host after colonization and dominant niche in the host intestine 34,35 . To investigate the accurate effects of the CPP supplementation, we performed a long‐term study in young layer chicks.…”
Section: Discussionmentioning
confidence: 99%
“…33 Exogenous probiotics have a subtle physiological effect on the host after colonization and dominant niche in the host intestine. 34,35 To investigate the accurate effects of the CPP supplementation, we performed a long-term study in young layer chicks. Similar to the results of these previous studies, we found that dietary supplementation with CPP significantly increased growth performance and reduced diarrhea, and that the effects of CPP supplementation were similar to those of CTC supplementation in layer chicks.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies from various animal models in gut microbiota investigations, such as GF (complete absence of microbial exposure) animals, SPF (specific pathogen-free) animals, antibiotic-treated (broad-spectrum antibiotic cocktails) animals, and animals exposed to pathogenic bacterial infections, suggest that the gut microbiota plays an important role in the regulation of anxiety, mood, and cognition, indicating the possibility of using probiotics to modify the gut microbiota to control impulsive and compulsive behaviors in patients with neuropsychiatric disorders [ 158 , 159 , 160 , 161 ]. Like mammals, the gut microbiome plays a critical role in poultry health and welfare [ 119 , 162 , 163 ]. Laying hens showing high or low FP have different gut microbial populations [ 27 , 94 , 95 , 164 ] and metabolite profiles [ 96 , 97 ].…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%